On the Mechanism of Rust Exfoliation in Marine Environments. Issue 2 (1st January 2017) - Morcillo, M.; Chico, B.; de la Fuente, D.; Alcántara, J.; Wallinder, I. Odnevall; Leygraf, C.
Abstract : Based on exposures in chloride-rich field and laboratory atmospheres, a mechanism of rust exfoliation of carbon steel is proposed. Key ingredients are structural transformations between main rust phases (goethite, lepidocrocite, spinel oxides and akageneite) during varying exposure conditions and their large difference in molar volume with a factor of five between the most compact and least compact rust phase. Akaganeite transformed to spinel results in volume contraction, lepidocrocite to spinel in volume expansion and in both cases stresses are introduced in the rust multilayer. At sufficiently high chloride deposition rates (∼300 mg/m 2 ·d), the rust multilayer eventually detaches resulting in rust exfoliation.